Legal Scope of the Mediation and Problem of Applicability - Kaija, Sandra; Kudeikina, Inga (European Journal of Sustainable Development, 2018)
Mediation can be described as a multi-functional legal tool serving the mission of law, which is to ensure public balance, justice and order. This is possible owing to the legal nature of mediation, because it is essential not to merely solve a dispute but to understand its cause during the mediation process. Nowadays, mediation is equally effective in cases associated with civil disputes and criminal offences to attain understanding-based reconciliation between the victim and the perpetrator. However, the voluntary nature of mediation may hinder the achievement of a positive result in some situations. The aim of this article is to examine the legal scope of mediation with a view to determining to which extent mediation can be applied in civil and criminal proceedings and answering the question of whether possibilities offered by mediation are effectively used by law. The added value of mediation is the alignment of parties’ interests by means of active cooperation and the elimination of the cause of the dispute. Contrary to enforcement mechanisms, such as the execution of court rulings, mediation enables more effective use of possibilities provided by law as a social system and alleviation of tension caused by disputes in society. This research employs general scientific methods, such as analysis, induction and deduction and interpretation of law. The research is based on legislation, scientific literature and case-law. Keywords: Mediation, criminal proceedings, civil proceedings, settlement and resolution of disputes